Konsep Kuasi- dalam Bahasa Inggris - Ikmi Nur Oktavianti (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Some languages have its universal features such as subject, object, and copula. However, each language has its specific features regarding the universal ones, including in English. There are some linguistic elements similar to subject, object, and copula in English for they inherit their basic characteristics. Those elements are called quasi- and specific in English. Therefore, this paper will attempt to describe the causes and the processes of the emergence of those quasi elements. By doing so, the comprehensive analysis of quasi- will be obtained.